Examining the influence of perceived value and online game addiction on in-game purchase intention with the mediating role of loyalty of Genshin Impact players from the Philippines: An analysis of an open-world action role-playing game - Chen, Xiao Shi Sofia Sandra (Animo Repository, 2022)
The game industry has been continuously growing in the late years. In 2020, the release of Genshin Impact, an open-world action role-playing game (RPG), created an enormous influence that attracted players worldwide. This research paper examines how Online Game Addiction and Perceived Value affect In-game Purchase Intention with the mediating effect of Loyalty of the Genshin Impact players in the Philippines. The researchers used Jamovi, Statistica, and SPSS Hayes PROCESS to interpret and analyze the results of the data gathered. The results show that Online Game Addiction and Perceived Value, including the sub-variables Playfulness, Connectedness, Access Flexibility, Rewards, and Good Price, significantly influence Loyalty in the game Genshin Impact. Moreover, Online Game Addiction significantly influences In-game Purchase Intention. However, only some of the sub-variables of Perceived Value significantly influence In-game Purchase Intention in the game Genshin Impact; Access Flexibility is the only sub-variable of Perceived Value that does not significantly influence In-game Purchase Intention. In line with the results, recommendations were provided for Genshin Impact’s shareholders and project team. Besides, future researchers were provided with recommendations as well about different possibilities for future research.Keywords: online mobile game, Online Game Addiction, Perceived Value, Loyalty, In-game Purchase Intention, Genshin Impact